Diseño de propuesta para la optimización y automatización de líneas de producción de los laboratorios Herbacol Colombia - Plazas Forero, Billy Jeison (Universidad Antonio Nariño, 2023)
The present investigation has as purpose of the study, analysis and proposal for improvements to the production lines of the laboratories Herbacol Colombia Ltda., based on the evaluation,optimization and automation of processes production of the plant located in the Municipality of Mosquera Cundinamarca, eeks to generate benefits in plant performance, reduce production costs, determine the supply of equipment and machinery on the market that expands its productive capacity, rationalize production times manufacturing, and progressively increase the business competitiveness in the market of products for body and hair care. ​